Motivasi Belajar Mahasiswa Mengikuti Pembelajaran Struktur Dan Perkembangan Hewan I, Selama Pandemi Covid-19 Pada Program Studi Pendidikan Biologi, Universitas Cenderawasih - Megawati, Ruth (INSTITUT AGAMA ISLAM NEGERI AMBON, 2021)
Teaching and learning activities are a core part of education. Everything that has been programmed will be carried out in the teaching and learning process. The learning process is an inseparable part of the learning effort. Where learning is a complete change in a person. So that motivation which is an encouragement both from within and from outside a person greatly affects the learning process. This research is a quantitative descriptive type, which aims to describe student learning motivation, especially those who take the animal structure and development course I (SPH I), during the covid-19 pandemic at the Cenderawasih University biology education study program. The research sample was 43 students who were taken by saturated sampling technique, which used all the population as research samples. The method of data collection is by using a questionnaire that is given online through filling out google forms, as well as interviews to confirm / confirm the results of the questionnaire. The instruments used are open and closed questionnaires to collect data on student motivation, as well as interview guidelines conducted online and offline. Based on the results and discussion, it can be concluded that the student's motivation in following the SPH I course with blended learning (online and offline mixed learning) both intrinsic motivation and extrinsic motivation is in the medium category. With each percentage of 77.06% for intrinsic motivation and 73.5% for extrinsic motivation Keywords: learning motivation, covid-19 pandemic